Probing Biothiols Using a Red‐Emitting Pyridoxal Derivative by Adopting Copper(II) Displacement Approach and Cell Imaging. Issue 9 (24th August 2022) - Bhardwaj, Vinita; Patel, Dhvani A.; Majeed, S. Abdul; Sahul Hameed, A. S.; Aatif, Mujthaba A.; Kumar, Ashok S. K.; Sahoo, Suban K
Abstract: An aggregation‐induced emission (AIE) active Schiff base L was obtained by reacting pyridoxal and 2‐hydroxy‐1‐naphthaldehyde with p‐ phenylenediamine in two simple steps. The colorimetric, UV/VIS and fluorescence studies of L revealed that the yellow emissive L (λem =540 nm, λex =450 nm) in pure DMSO turned to a red‐emissive L, when the poor solvent fraction (HEPES buffer, 10 mM, pH 7.4) was increased above 50 % in DMSO. The SEM and DLS results indicated the formation of self‐aggregates of L that restricted the intramolecular motion and promoted the excited state intramolecular proton transfer (ESIPT) process. The cations sensing ability of the AIEgen L was explored in HEPES buffer (5 % DMSO, 10 mM, pH 7.4), where Cu 2+ selectively quenched the fluorescence at 608 nm due to the chelation‐enhanced fluorescence quenching (CHEQ) effect with an estimated sensitivity limit of 0.9 μM. Subsequently, the in situ formed AIEgen L‐Cu 2+ complex was applied for the cascade detection of glutathione (GSH), cysteine (Cys) and homocysteine (Hcy). The decomplexation of Cu 2+ from the AIEgen L‐Cu 2+ by GSH, Cys and Hcy restored the quenched fluorescence emission of AIEgen L at 608 nm. With this Cu 2+ displacement approach, the concentration of Cys, Hcy and GSH can be detected down to 2.8 μM, 3.12 μM and 2.0 μM, respectively. The practical utility of AIEgen L and AIEgen L‐Cu 2+ was examined by monitoring the selective analytes in real environmental and biological samples, and also applied successfully for the cell imaging applications. Abstract :